Analisis Yuridis Penerapan Asas Equality Before the Law dalam Penanganan Tindak Pidana Pemerasan - Yusuf Hatorangan; M. Rizal (CV WAHANA PUBLIKASI, 2026)
The principle of equality before the law is a fundamental principle of the rule of law that guarantees equal legal status and treatment for every person regardless of social status, position, or profession. However, its implementation in criminal law enforcement may face challenges, particularly when the alleged perpetrator is a law enforcement officer. This study aims to analyze the legal regulation and implementation of the principle of equality before the law in handling the crime of extortion involving members of the Indonesian National Police and civil society, as well as to identify factors that influence its implementation. This study employs a normative juridical method using statutory, conceptual, and comparative approaches. Legal materials consisting of primary, secondary, and tertiary sources were collected through library research and analyzed qualitatively and normatively. The findings indicate that the principle of equality before the law has a strong constitutional and legal basis and requires criminal proceedings to be conducted objectively, professionally, transparently, and without discrimination. In handling extortion cases, both police officers and civilians are subject to general criminal proceedings. Police officers, however, are additionally subject to professional ethical and disciplinary mechanisms, which constitute supplementary responsibilities and cannot replace criminal liability. The analysis further shows that differences in treatment may arise from law enforcement integrity, institutional culture, transparency, supervision, and the potential influence of institutional status. Therefore, consistent and accountable law enforcement is necessary to ensure that the handling of extortion cases is determined by the alleged criminal conduct and applicable legal standards rather than the perpetrator’s institutional position.